PWE-099 Desmoid Tumours in Familial Adenomatous Polyposis: Our Experience. (17th August 2016) - Kane, EG; Delamere, S; Garforth, E; Heath, R; Rooney, P
Abstract : Introduction: Desmoid tumours are rare, benign, non-metastasising fibromatoses that affect 8–23% of patients with FAP. Desmoid disease poses significant morbidity through local compression and obstruction. There is an increased risk in females, pregnancy, those with germline mutation of the APC gene beyond codon 1399 and previous abdominal surgery. Management requires a balance of chemoprophylaxis and careful surgical intervention. We aimed to evaluate our local investigation and management of patients with FAP and desmoid tumours with respect to published guidance. Methods: Patients with FAP who are on the colorectal database who were known to have desmoid disease were identified. Data was collected retrospectively from case notes, ICE and PACS systems. Management of each patient was compared to the St Mark's Polyposis Registry guidance and published literature. Results: There are 41 patients with FAP in our colorectal database (25 female, 16 male). Eleven patients from eight families were identified as having desmoid disease (six female, five male). Ten of these had desmoid tumours; one only postoperative desmoplastic reaction. The median age at diagnosis was 33 (range 8–49). Of the 10, all had undergone colectomy (five restorative proctocolectomy, three ileorectal anastomosis, two panproctocolectomy (eight prophylactically, two for malignancy). Three patients have had excision of desmoid tumours; all abdominal wall tumours. Six patients have been managed conservatively with observation, chemoprophylaxis and ureteric stenting for managing complications of compression. All patients have been kept under surveillance. One patient died following bowel perforation, one following recurrent bowel obstruction with inoperable mesenteric desmoid disease. Genetic testing was performed on the majority but specific mutational analysis was available for only 67% of patients. 6 of 8 of the patients with mutations in the desmoid region have developed desmoid tumours. Conclusion: Mortality in our patient group from desmoid disease is higher than that from colorectal cancer and periampullary tumours, in line with national reported data. Prophylactic colectomy has been suggested to increase risk of developing desmoid disease especially with mutations in the desmoid region. Our results show that our patients are being managed appropriately but knowledge of location of germline mutation is strongly advised prior to offering prophylactic colectomy and management of solid desmoid tumours. In those with a higher risk of developing desmoid tumours, there may be an argument to continue endoscopic surveillance for as long as possible. Reference: 1 Speake, et al . Desmoid tumours in patients with familial adenomatous polyposis and desmoid region adenomatous polyposis coli mutations. Br J Surg 2006;93 (Suppl 1):21. Disclosure of Interest: None Declared